2018
DOI: 10.21608/jfds.2018.35150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adding Inulin as a Fat Replacer on the Characteristics of Yoghurt

Abstract: The effects of substituting milk fat with different levels of inulin as a fat replacer on the chemical, microbiological and sensory characteristics of yoghurt were examined. Samples of yoghurt were kept in refrigerator at (5± 2Cº), and examined when fresh, and after 2, 3 and 7 days of storage. Chemical composition, microbiological contents and sensory characteristics were examined. The obtained results indicated that addition of inulin resulted in a significant increase in the total solids, moisture contents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…The results were consistent with those obtained by Sahan [20] for kashar cheese, who suggested that increased fat substitution in cheese may be resulting in increased DM % retention in low-fat cheese. Furthermore, the findings were comparable to those of Khodear [21] who discovered that adding inulin resulted in a considerable increase in total solids, and the production of titrated acidity. Sousa [22] ascribed the increase in WSN % to the hydrolysis of whole casein by residual chymosin and, to a minor extent, the indigenous milk proteinase, plasmin, and the proteolytic activity of the cheese bacterial culture.…”
Section: Discussionsupporting
confidence: 85%
“…The results were consistent with those obtained by Sahan [20] for kashar cheese, who suggested that increased fat substitution in cheese may be resulting in increased DM % retention in low-fat cheese. Furthermore, the findings were comparable to those of Khodear [21] who discovered that adding inulin resulted in a considerable increase in total solids, and the production of titrated acidity. Sousa [22] ascribed the increase in WSN % to the hydrolysis of whole casein by residual chymosin and, to a minor extent, the indigenous milk proteinase, plasmin, and the proteolytic activity of the cheese bacterial culture.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, inulin has various functional properties, among others demonstrating good gelability. One of the most important is its fat mimetic property, which is successfully used in the production of mayonnaise, margarine, yogurts and sponge cakes [5][6][7]. The incorporation of this fiber into the food composition (at least 3 g/100 g portions) allows the product to be labeled with a nutrition claim, and when it provides a 12 g dose per day a health claim can be used [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that consumption of these products provides a number of health benefits due to live cultures of lactic bacteria (probiotics) [11,12]. The inclusion of various additives in the fermented milk product composition may increase their nutritional and health value [6,10,13,14], and also changes their rheological and textural properties [11]. The application of 1-2% inulin addition to skimmed cow's milk enables the production of yogurt with acceptable quality and characteristics comparable to yogurt obtained from full-fat cow's milk [6].…”
Section: Introductionmentioning
confidence: 99%
“…A adição do preparado de frutas verdes em todas as formulações também contribuiu na textura, devido ao aumento do teor de sólidos e da presença de goma xantana e amido modificado que auxiliam na viscosidade. Estudos na literatura corroboram com os resultados obtidos na aceitação sensorial de leites fermentados com adição de inulina e saborização com frutas (Da Silva et al 2017;Khodear et al, 2018;Maestri et al, 2014;Munhoz et al, 2019).…”
Section: F1unclassified